2006
DOI: 10.1016/j.athoracsur.2006.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure and Metabolic Changes After Lung Volume Reduction Surgery for Emphysema

Abstract: Background. Oxygen consumption volume (VO 2 ) and resting energy expenditure are increased in emphysema because of impaired respiratory function and mechanics, with greater oxygen cost of breathing and altered metabolism. We hypothesized that lung volume reduction surgery may improve energy expenditure and metabolism.Methods. In this 1-year prospective study, 30 patients with moderate-to-severe emphysema underwent bilateral lung volume reduction surgery; 28 similar patients, who refused operation, followed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…As previously reported, 13 the reduction in residual volume was significantly correlated with the increment of FFM ( ϭ Ϫ 0.49; p Ͻ 0.02) and FM ( ϭ Ϫ 0.55; p Ͻ 0.009). In addition, the reduction of residual volume was significantly correlated with the increase in ghrelin ( ϭ Ϫ 0.52; p Ͻ 0.01), with the reduction in leptin corrected for FM ( ϭ 0.50; p Ͻ 0.02), and only marginally with the decrease in the HOMA-IR ( ϭ 0.35; p ϭ 0.07).…”
Section: Correlation Analysissupporting
confidence: 68%
See 2 more Smart Citations
“…As previously reported, 13 the reduction in residual volume was significantly correlated with the increment of FFM ( ϭ Ϫ 0.49; p Ͻ 0.02) and FM ( ϭ Ϫ 0.55; p Ͻ 0.009). In addition, the reduction of residual volume was significantly correlated with the increase in ghrelin ( ϭ Ϫ 0.52; p Ͻ 0.01), with the reduction in leptin corrected for FM ( ϭ 0.50; p Ͻ 0.02), and only marginally with the decrease in the HOMA-IR ( ϭ 0.35; p ϭ 0.07).…”
Section: Correlation Analysissupporting
confidence: 68%
“…32 When compared to maximal medical and rehabilitation therapy, LVRS provides an immediate and prolonged improvement of functional indexes, static volumes, exercise capacity, nutritional status, and quality of life. 12,13 After LVRS, the amelioration of gas exchange capacity and the reduction of the oxygen cost of breathing were correlated with weight gain 33 and FFM recovery. 34,35 We also showed that improvements in body weight and composition, bone mineral density, and resting energy expenditure correlated with the surgical reduction of residual volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LVRS patients continuing oral steroids experienced significant ameliorations compared with the RR patients, despite comparable dosage, as previously shown [13,15]; this observation persisted throughout the study period.…”
Section: Respiratory Evaluationsupporting
confidence: 63%
“…Respiratory muscles V9O 2 was calculated as the proportion of V9O 2 of respiratory muscles (V9O 2 ,Resp%) compared to total V9O 2 , using measured and predicted REE values. Measured REE and V9O 2 were then corrected for FFM [15].…”
Section: Energetic Metabolism Evaluationmentioning
confidence: 99%